Sistem Informasi Penjadwalan Kendaraan Pada CV. Serin Transport Berbasis Web - Muhammad Rikza Nashrulloh; Ridwan Setiawan; M Rizki Nur Jamil; Deni Heryanto (Jurnal Algoritma, 2022)
CV Serin Transport is a subsidiary of PT Fajar Prakasa, CV Serin Transport is engaged in goods delivery services. Services at CV Serin Transport include the distribution of fertilizers, both subsidized and non-subsidized, as for delivery areas including Garut, Ciamis, Tasikmalaya, and Sumedang districts. Problems with CV Serin Transport in scheduling Fleet departures still use manual, namely only using Microsoft excel is also data storage, data security, and presentation of information that is less efficient and effective, as well as recapitulation by the Administration which is done by one person. If a Fleet asks for departure schedule information for the delivery of goods, the result is that it becomes an obstacle to work and disrupts time efficiency and reduces company performance and profits. Vehicle Management Information System at CV Serin Transport, which was built to record goods delivery scheduling and produce a report on the scheduling of goods shipments to facilitate the presentation of information to Owners and Fleet. This Vehicle Management Information System uses the RAD (Rapid Application Development) Method using several stages, namely business modeling, data modeling, process modeling, application development, testing, and sales. The expected results in making the Vehicle Management System at CV Serin Transport can optimize the performance of the company.